Hypocholesterolemic Effect of Mature Leaf Extract of Sugarcane, Saccharum officinarum (Linnaeus, 1753), in Induced Rats - Raamah Rosales (ASEAN Journal of Science and Engineering, 2021)
Hypercholesterolemia is a common health risk factor for various cardiovascular diseases. The use of the medicinal plant as an alternative treatment is gaining much attention due to the reported adverse effects of statins on liver and muscle toxicity.  This study aimed to determine the hypocholesterolemic properties of the mature leaf of the sugarcane plant using hypercholesterolemia-induced rats. Thirty-two Sprague Dawley rats were divided into 4 groups and fed with a normal diet and a 4% high cholesterol diet. The dose conversion was based on the human dose to surface area ratio of 0.025 at 1mg/20g rat body weight. The treatment with mature leaf extract of S. officinarum significantly lowered the cholesterol levels. The hypocholesterolemic activity and percent reduction of the plant extract were comparable to the effects of a synthetic drug, Fluvastatin, in lowering the cholesterol levels. This study presents the potential of mature leaf extract of S. officinarum as an alternative therapeutic strategy for hypercholesterolemia.